Jilidan ACTA MEDIKA INDONESIA: The Indonesian Journal of Internal Medicine Vol.49 No. 2-4, 2017 dan Vol.50 No.1-3, 2018 (Per. Dokter Sp. P. Dalam Indo, 2018)
Jilidan ACTA MEDIKA INDONESIA: The Indonesian Journal of Internal Medicine Vol.49 No. 2-4, 2017 dan Vol.50 No.1-3, 2018